Seasonal and geographic dynamics in bioproperties and phytochemical profile of Limonium algarvense Erben - Pereira, Catarina Guerreiro (2024)
This study delved into the influence of ecological and seasonal dynamics on the synthesis of secondary metabolites in the medicinal halophyte Limonium algarvense Erben, commonly known as sea lavender, and examined their antioxidant and anti-inflammatory properties. Aerial parts of sea lavender were systematically collected across winter, spring, summer, and autumn seasons from distinct geographic locations in southern Portugal, specifically “Ria de Alvor” in Portimão and “Ria Formosa” in Tavira. The investigation involved determining the total polyphenolic profile through spectrophotometric methods, establishing the chemical profile via liquid chromatography electrospray ionization quadrupole time-of-flight mass spectrometry (LC-ESI-QTOF-MS/MS), and evaluating in vitro antioxidant properties using radical and metal-based methods, along with assessing anti-inflammatory capacity through a cell model. Results unveiled varying polyphenol levels and profiles across seasons, with spring and autumn samples exhibiting the highest content, accompanied by the most notable antioxidant and anti-inflammatory capacities. Geographic location emerged as an influential factor, particularly distinguishing plants from “Ria de Alvor”. Seasonal fluctuations were associated with environmental factors, including temperature, which, when excessively high, can impair plant metabolism, but also with the presence of flowers and seeds in spring and autumn samples, which also seems to contribute to elevated polyphenol levels and enhanced bioproperties of these samples. Additionally, genetic factors may be related to differences observed between ecotypes (geographical location). This study underscores sea lavender’s potential as a natural source of antioxidant and anti-inflammatory agents, emphasizing the significance of considering both geographic location and seasonal dynamics in the assessment of phenolic composition and bioactive properties in medicinal plant species.